Revolutions in Neuroscience: Tool Development - Bickle, John (Frontiers in Systems Neuroscience, 2016)
Thomas Kuhn’s famous model of the components and dynamics of scientific revolutions is still dominant to this day across science, philosophy, and history. The guiding philosophical theme of this paper is that, concerning actual revolutions in neuroscience over the past sixty years, Kuhn’s account is wrong. There have been revolutions, and new ones are brewing, but they do not turn on competing paradigms, anomalies, or the like. Instead, they turn exclusively on the development of new experimental tools. I adopt a metascientific approach and examine in detail the development of two recent neuroscience revolutions: the impact of engineered genetically mutated mammals in the search for causal mechanisms of “higher” cognitive functions; and the more recent impact of optogenetics (and DREADDs). The two key metascientific concepts I derive from these case studies are a revolutionary new tool’s motivating problem, and its initial and second-phase hook experiments. These concepts hardly exhaust a detailed metascience of Tool Development experiments in neuroscience, but they get that project off to a useful start and distinguish the subsequent account of neuroscience revolutions clearly from Kuhn’s famous model. I close with a brief remark about the general importance of molecular biology for a current philosophical understanding of science, as comparable to the place physics occupied when Kuhn formulated his famous theory of scientific revolutions.